Long Noncoding RNAs of the Arterial Wall as Therapeutic Agents and Targets in Atherosclerosis - Holdt, Lesca M.; Kohlmaier, Alexander; Teupser, Daniel (Thrombosis and Haemostasis, 2019)
Long noncoding ribonucleic acids (lncRNAs) have been defined as transcripts which are > 200 ribonucleotides in size and are not translated into protein. Recent work has shown that many lncRNAs do have specific molecular functions and biological effects, and are involved in a growing number of diseases, including atherosclerosis. As a consequence, lncRNAs are also becoming interesting targets for therapeutic intervention. Here, we focus on lncRNAs which are expressed in the arterial wall, and describe potential RNA therapeutic approaches of atherosclerosis by manipulating lncRNAs without affecting genome deoxyribonucleic acid content: Starting out with an overview of all lncRNAs that have so far been implicated in atherosclerosis by in vivo studies, we describe methodologies for their activation, inactivation, and RNA sequence manipulation. We continue by addressing how artificial (nonnative) therapeutic lncRNAs may be designed, and which molecular functions these designer lncRNAs may exploit. We conclude with an outlook on approaches for chemical lncRNA modification, RNA mass production, and site-specific therapeutic delivery.
Keywords: transcription; splicing; lncRNAs; circRNAs; gene expression